Biomonitoring of the Traffic Related Heavy Metal Pollution Using Roadside Plants as Possible Bioindicators During Different Seasons - Huma Naveed, Naima; Iram Batool, Aima; Hameed, Uzma; Ali, Aamir; Fayyaz ur Rehman, Muhammad; Sher, Muhammnad; Ali, Saima; Faiz, Samia (Asian Journal of Chemistry, 2012)
The degree of heavy metal pollution in Sargodha city was determined on different selected areas using three different plants as bioindicator. The leaf samples of Dalbergia sissoo Roxb., Prosopis juliflora L. and Eucalyptus spp. were collected from different sites including industrial, roadside, urban, suburban and rural in summer and winter season and analyzed for heavy metals Fe, Mn, Co and Ni concentration. These elements were detected and estimated by using atomic absorption spectrophotometer. Results of correlation analyses showed significant correlations among Fe, Mn, Co and Ni contents in leaf samples. Among these Fe was present in highest concentration in plant leaves during summer and Ni was present in lowest concentration during summer. There exist a significant correlation between these heavy metals (Fe, Mn, Co, Ni) concentration in these plant samples. Thus leaves of Dalbergia sissoo Roxb., Prosopis juliflora L. and Eucalyptus spp. were found to be the most suitable bioindicator of heavy metal pollution.